Importance of wellbeing strategies at the workplace: A case study of organizations in Hungary - Murtaza, Shah Ali; Kun, Ágota; Molnár, Edina (Acta Carolus Robertus, 2023)
Improving wellbeing at the workplace is the most talked-about topic in human resource management these days. Organizations now are not just focusing on the output of employees, but they are also focusing on how they manage to give input and how they feel at the workplace. Substantial research has been conducted in the area which reveals that the sustainable performance of employees is directly related to the mental health, vitality, and wellbeing of employees. Organizations need to put employee vitality and wellbeing as a priority in their operations. This study aims to understand the factors that influence the well-being of employees in the workplace and how they can improve. The study also reveals how the organizations that have a sound wellbeing strategy impact the overall performance and mental health of employees working in those organizations. 162 respondents filled the questionnaire. The data was analyzed using SPSS. The results show that the size of the budget for well-being and the existence of a well-being strategy impacts the ability of companies to offer well-being programs. Another important finding from the research is that the geographical location of the company impacts the existence of well-being strategies in companies, and they can differ depending on the geographical location. It was also found that if a company needs a well-being strategy, it is not impacted by the size of the company. The more companies invest in ensuring the wellbeing and mental health of employees, the more the employee motivation and meaningfulness at work improves, resulting in better performance.